Customer tech savviness, business partner, and marketing performance: Mediating role of business model innovation - Nina Fapari Arif; Muhamad Ridwan; Siti Khusnul Rifani; Riria Zhandy Mirahati (Jurnal Fokus Manajemen Bisnis, 2026)
Small and medium-sized enterprises are increasingly required to adapt to customers' tech-savviness and foster strong collaborative alliances with business partners to sustain effective marketing outcomes. This investigation seeks to explore the impact of customer technological savviness, collaborative efforts with business partners, innovation in business models, and effective marketing strategies. Furthermore, it examines the mediating role of business model innovation in the relationship between external influencers and marketing outcomes. A quantitative research design was adopted, employing partial least squares structural equation modeling to analyze data gathered from 187 small and medium-sized enterprises in the Indonesian food and beverage industry, selected through purposive sampling. Marketing performance is driven by customers' tech-savviness and business model innovation, but not by business partners. Furthermore, both customer tech-savviness and business partners drive business model innovation. Business model innovation bridges the gap, allowing both customers' tech-savviness and business partners to drive marketing performance. These findings underscore the pivotal mediating role of business model innovation as a strategic mechanism that translates digital readiness and partnership strength into superior marketing outcomes. This study contributes to the literature on the digital transformation of small and medium-sized enterprises by providing empirical evidence of the mediating role of business model innovation in emerging markets. It expands upon current research by framing customer tech savviness and collaboration with business partners as essential external facilitators of innovation-driven marketing performance. The findings have practical implications for managers seeking to capitalize on digital customer capabilities and collaborative networks to achieve sustainable competitive advantages.